Amino Acids and Their Metabolism in Atherosclerosis. Issue 3 (March 2019) - Nitz, Katrin; Lacy, Michael; Atzler, Dorothee
Abstract : As a leading cause of death worldwide, cardiovascular disease is a global health concern. The development and progression of atherosclerosis, which ultimately gives rise to cardiovascular disease, has been causally linked to hypercholesterolemia. Mechanistically, the interplay between lipids and the immune system during plaque progression significantly contributes to the chronic inflammation seen in the arterial wall during atherosclerosis. Localized inflammation and increased cell-to-cell interactions may influence polarization and proliferation of immune cells via changes in amino acid metabolism. Specifically, the amino acids L-arginine (Arg), L-homoarginine (hArg) and L-tryptophan (Trp) have been widely studied in the context of cardiovascular disease, and their metabolism has been established as key regulators of vascular homeostasis, as well as immune cell function. Cyclic effects between endothelial cells, innate, and adaptive immune cells exist during Arg and hArg, as well as Trp metabolism, that may have distinct effects on the development of atherosclerosis. In this review, we describe the current knowledge surrounding the metabolism, biological function, and clinical perspective of Arg, hArg, and Trp in the context of atherosclerosis.